Penerapan Teori Sosial Kognitif Bandura dalam Pembelajaran Anak Usia Dini Melalui Observasi dan Peniruan Perilaku Positif - Euis Trismayanti; Ai Rismayanti; Eli Rahmawati (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to analyze the application of Albert Bandura’s Social Cognitive Theory in early childhood education through the processes of observation and imitation of positive behavior. Bandura’s theory emphasizes that learning results from the dynamic interaction among personal, environmental, and behavioral factors. In the context of early childhood education, observational learning and modeling serve as effective strategies for character formation and the development of children’s social competence. This research employs a literature review approach and limited classroom observation in early childhood institutions. The findings indicate that the implementation of this theory can be carried out through teachers’ positive behavioral modeling, role-playing activities, and reinforcement of prosocial behavior. These strategies have been shown to enhance children’s social awareness, empathy, and self-regulation. Therefore, the application of Bandura’s Social Cognitive Theory significantly contributes to the development of character and adaptive behavior in early childhood, providing a strong conceptual foundation for character education curriculum design in early childhood learning environments.